Plano do projeto: Implementação de um escritório de projetos na Incubadora Tecnológica de Santa Maria (ITSM) - Rosa, Douglas da (Universidade do Vale do Rio dos Sinos, 2015)
The development of business projects in technological incubators is an entrepreneurial challenge, which can be better managed when there strategies and tools most appropriate to projects. The aim of this paper is to prepare a study on the actual needs and knowledge of the Technological Incubator of Santa Maria (ITSM) for the project management (PM) as well as project management office (PMO) and propose an implementation plan for a PMO to best practices listed in the guide PMBOK (2013). Thus, the first part of this paper configures a case study, and the second an applied research. In the first part, so it is prepared a business case that includes: by a quantitative approach, the degree of general knowledge in project management to the administration and incubated ITSM; the project management maturity of the ITSM through the Model PRADO MMGP; the positioning of the PMO in the ITSM; and the main functions that complies with the needs and desired maturity of this PMO with the PMO MIX MANAGER tool. In the second part of this paper the project plan includes nine areas of the PMBOK (2013): integration, scope, time, cost, quality, resources, communications, risk and acquisition. Through this paper, so it was possible to determine that the PMO can be an important support for ITSM achieve its strategic objectives, as there are opportunities and receptivity to the use practices and PM methodologies despite the low level of maturity in PM that organization currently has. Thus, the project implementation plan of a PMO in the ITSM up front applies the requirements of this technological incubator.
Keywords: Incubadora tecnológica; Escritório de projetos; Gestão de projetos; PMBOK; Technological incubator; Project management office; Project management